2012
DOI: 10.1186/2040-7378-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on the efficacy of bone marrow mononuclear cell transplantation in experimental stroke

Abstract: Bone marrow-derived mononuclear cells (BM MNC) have been effectively used to treat experimental stroke. Most of the preclinical trials have been performed in young and healthy laboratory animals, even though age and hypertension are major risk factors for stroke. To determine the influence of age on the properties of BM MNCs after cerebral ischemia, we compared the efficacy of aged and young BM MNC in an in vitro model of cerebral hypoxia and in an adapted in vivo model of stroke. Human BM MNCs were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…Degree of heterogeneity in the pooled estimates is represented at I 2 statistic. The studies included in meta-analysis of absolute 5,6,41,54 and relative 39,40,44,46,49,50 decrease in infarct size are cited.…”
Section: Figurementioning
confidence: 99%
“…Degree of heterogeneity in the pooled estimates is represented at I 2 statistic. The studies included in meta-analysis of absolute 5,6,41,54 and relative 39,40,44,46,49,50 decrease in infarct size are cited.…”
Section: Figurementioning
confidence: 99%
“…Although BM cells play an important role in hypertensiveinduced diseases (Wagner et al, 2012) and that 2K1C hypertension leads to increased production of ROS , the impact of this renovascular hypertension on apoptosis in BM cells has not yet been investigated in this murine model. Therefore, the present study was designed to test the hypothesis that the augmented production of superoxide anions ( O 2 -) and hydrogen peroxide (H 2 O 2 ) leads to DNA fragmentation and apoptosis in the 2K1C hypertension model.…”
mentioning
confidence: 99%
“…Furthermore, to minimize the risk for false-negative interpretation of the results a priori, sample size calculations were performed based on the data derived from previous studies of our group. 16 In fact, hardly any previous study applying cord blood therapy for ischemic injury reported on sample size calculations and if so, these studies were powered to detect improvements in primary outcome parameters of X40%. 44 Nevertheless, it has to be mentioned that s.d.…”
Section: Discussionmentioning
confidence: 99%
“…were derived from former experiments and set to 20% of the area under the curve for the ladder rung test and 15% for the modified neurologic severity score (mNSS). 16 Thus, the required sample size (two-tailed) was 12 animals per group for the ladder rung test and seven animals per group for the mNSS. Secondary endpoints comprised infarct volume and secondary hemispheric atrophy on MRI.…”
Section: Methodsmentioning
confidence: 99%